Receptor of Advanced Glycation End Products Deficiency Attenuates Cisplatin-Induced Acute Nephrotoxicity by Inhibiting Apoptosis, Inflammation and Restoring Fatty Acid Oxidation - Wang, Qiang; Xi, Yuemei; Chen, Binyang; Zhao, Hairong; Yu, Wei; Xie, De; Liu, Weidong; He, Furong; Xu, Chenxi; Cheng, Jidong (Frontiers in Pharmacology, 2022)
Cisplatin is a widely used and potent anti-neoplastic agent, but severe and inescapable side effects in multiple normal tissues and organs limit its application, especially nephrotoxicity. Molecular mechanisms of cisplatin nephrotoxicity involve mitochondrial damage, oxidative stress, endoplasmic reticulum stress, inflammation, apoptosis, necroptosis, etc. Receptor of advanced glycation end products (RAGE) is a multiligand pattern recognition receptor, engaged in inflammatory signaling and mitochondrial homeostasis. Whether inhibition of RAGE alleviates cisplatin-induced nephropathy has not been investigated. Here, we revealed that RAGE deficiency attenuates cisplatin-induced acute nephrotoxicity, as evidenced by reduced apoptosis, inflammation, lipid accumulation, restored mitochondrial homeostasis and fatty acid oxidation in renal tubular epithelial cells (TECs). In vitro, the RAGE-specific inhibitor FPS-ZM1 attenuated the cisplatin-induced decrease of cell viability and fatty acid oxidation in the normal rat renal TEC line NRK-52E cells. Taken together, RAGE knockout mitigated cisplatin-induced acute nephrotoxicity by inhibiting apoptosis, inflammation, and restoring fatty acid oxidation in TECs, suggesting that RAGE inhibition could be a therapeutic option for cisplatin-induced acute nephrotoxicity.